Effect of superdisintegrants on formulation of taste masked fast disintegrating Ciprofloxacin tablets - Jain, Nilesh; Mandal, Sumain; Banweer, Jitendra; Jain, Surendra (International Current Pharmaceutical Journal, 2012)
The present investigation deals with the formulation of taste masked fast disintegrating tablets of Ciprofloxacin that disintegrate in the oral cavity upon contact with saliva and thereby improve therapeutic efficacy. Ciprofloxacin is a synthetic chemotherapeutic antibiotic of the fluoroquinolone drug class. It is a second-generation fluoroquinolone antibacterial that kills bacteria by interfering with the enzymes that cause DNA to rewind after being copied, which stops synthesis of DNA and protein. It may also be used to prevent or slow anthrax after exposure. The influence of superdisintegrants, crospovidone and sodium starch glycolate on disintegration time, wetting time and water absorp-tion ratio were studied. Tablets were evaluation for weight and thickness variation, disintegration time, drug content, in vitro dissolution, wetting time and water absorption ratio. The in vitro disintegration time of the best fast disinte-gration tablets was found to be within 36 seconds. Tablets containing crospovidone (40%) exhibits quick disintegration time than tablets containing sodium starch glycolate. The fast disintegrating tablets of ciprofloxacin with shorter disintegration time, acceptable taste and sufficient hardness could be prepared using crospovidone and other excipients at optimum concentration. Key Words: ciprofloxacin; sodium starch glycolate; crospovidone; superdisintegrants; taste mask; fast disintegrating tablet. DOI: http://dx.doi.org/10.3329/icpj.v1i4.10059 International Current Pharmaceutical Journal 2012, 1(4): 62-67